1998
DOI: 10.1016/s0014-5793(98)00399-8
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional expression of a `fast' fungal kinesin

Abstract: Conventional kinesins are molecular motors that move towards the plus end of microtubules. In animal species, they have been shown to be remarkably conserved in terms of both their primary sequence and several physiological properties, including their velocity of movement. Here we report the cloning of Synkin, a homologue of conventional kinesin from the zygomycete fungus Syncephalastrum racemosum [Steinberg, Eur. J. Cell Biol. 73 (1997) 124^131] that is 4^5 times faster than its animal counterparts. Express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…However, only dynein (92,104) and three kinesin motors, kinesin-1, kinesin-3 (67,108), and kinesin-7 (63), have been shown to be essential for filamentous growth. In animal cells, kinesin-1 (conventional kinesin) and kinesin-3 (Unc104/Kif1A) are prominent organelle transporters (13,51), and these motors are also encoded by filamentous fungi (32,46,66,106,116,119,136,141), whereas they are absent from the yeast Saccharomyces cerevisiae. This suggests that both motors could play a role in long-distance transport in fungal hyphae.…”
Section: Microtubule-dependent Kinesins Support Polarized Hyphal Growthmentioning
confidence: 99%
“…However, only dynein (92,104) and three kinesin motors, kinesin-1, kinesin-3 (67,108), and kinesin-7 (63), have been shown to be essential for filamentous growth. In animal cells, kinesin-1 (conventional kinesin) and kinesin-3 (Unc104/Kif1A) are prominent organelle transporters (13,51), and these motors are also encoded by filamentous fungi (32,46,66,106,116,119,136,141), whereas they are absent from the yeast Saccharomyces cerevisiae. This suggests that both motors could play a role in long-distance transport in fungal hyphae.…”
Section: Microtubule-dependent Kinesins Support Polarized Hyphal Growthmentioning
confidence: 99%
“…Light chains are not essential for motor activity (Yang et al, 1990), but they are required for in vivo function (Gindhart et al, 1998;Rahmann et al, 1999). Conventional kinesins isolated from various fungal species (Steinberg and Schliwa, 1995;Lehmler et al, 1997;Steinberg, 1997;Grummt et al, 1998;Wu et al, 1998) share significant sequence homology and a similar domain structure with animal conventional kinesins (Kirchner et al, 1999). However, fungal kinesin purifies without light chains (Steinberg and Schliwa, 1996;Steinberg, 1997;Steinberg et al, 1998), and no conserved light chains are present in the genome of fungi, such as Neurospora crassa and Ustilago maydis (our unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…The representative myosin with the highest similarity is the skeletal muscle heavy polypeptide 2 (GB Accession #NP_659210) (Allen and Leinwand, 2002). Interestingly, it also shows significant similarity to NUF1 or SPC110 (yeast spindle poly-body spacer protein, Swiss-prot Accession #P32380) (Mirzayan et al, 1992;Kilmartin et al, 1993), centrosome protein 2 (CEP250/c-Nap1, Swiss-prot Novel structure proteins overexpressed in tumor cells N Sang et al Accession #Q9BV73; GB Accession #NP_009117) (Fry et al, 1998;Mayor et al, 2000Mayor et al, , 2002, centromeric protein E (Accession #Q02224) (Yen et al, 1992;Thrower et al, 1995;Chan et al, 1998), kinesin heavy chain (Synkin, Accession #O43093) (Grummt et al, 1998), and Spo15p (S. pombe sporulating protein, Accession #Q10411) (Ikemoto et al, 2000). A conserved domain search revealed that this region has a coiled-coil (Figure 5a and b).…”
Section: Conserved Motifs and Features Of The Predicted Peptidesmentioning
confidence: 99%